Sistem Manajemen Pengungsi Guna Meningkatkan Efektivitas Operasional BPBD Kota Batu Dalam Pendataan Dan Pemantauan Pengungsi - Ardiansyah, Muhammad Rizqi; Rosiani, Ulla Delfana; Yunhasnawa, Yoppy (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
Batu City is a region known for its natural beauty but also faces high risks of natural disasters such as landslides, earthquakes, and floods. The primary challenge faced by the Regional Disaster Management Agency (BPBD) of Batu City is the manual processing of refugee data. In emergency situations, such as post-disaster scenarios, time is crucial, and manual data collection, processing, and reporting can hinder the rapid response needed to assist refugees. Additionally, data mismatches and inaccuracies in logistics and kitchen needs pose serious problems. Therefore, there is a need for a refugee management information system to enhance the operational effectiveness of BPBD Batu City in data processing, real-time data monitoring, and ensuring the accuracy of logistics and kitchen needs data. This study employs a combination of design thinking and the spiral method for system development. Based on testing the impact of the application on BPBD's response showed an increase in response speed by 87.1%. This proves that the implemented system effectively enhances BPBD Batu's operational efficiency in refugee data collection and monitoring.